Probiotics ameliorate intestinal pathophysiology in a mouse model of Alzheimer’s disease - Kaur, Harpreet (Neurobiol Aging, 2020)
Evidence suggests that changes in intestinal microbiota may not only influence gastrointestinal function but also affect the central nervous system (CNS). However, it is unclear whether alteration of the intestinal microbiota affects progression or inflammatory aspects of Alzheimer’s disease (AD), one of the most common dementing neurodegenerative diseases. To understand the relationship of gut intestinal microbiota with AD pathology, wild type control (C57BL/6) mice were compared to a mouse line that has the human Aβ sequence knocked into the mouse APP gene (App(NL-G-F)). In addition, we used probiotics to manipulate the gut microbiota of these animals. Fecal samples were collected to examine the overall diversity in intestinal microbiota. To study brain and intestinal inflammation, biochemical and histological analyses were performed. Altered metabolic pathways that could be associated with AD or the probiotic-mediated changes were examined by quantifying eicosanoid and bile acid profiles in brain and serum using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). We observed that brain pathology was associated with intestinal dysbiosis and increased intestinal inflammation and leakiness in the App(NL-G-F) mice. However, modulating gut bacteria using probiotics significantly decreased intestinal inflammation and gut permeability with minimal effect on plaque deposition, cytokine levels, or gliosis in the brain. Mass spectrometry data revealed altered levels of several bile acids and prostaglandins in serum as well as in brain due to AD or probiotic supplementation. Our study characterizes intestinal dysfunction in an Alzheimer’s disease mouse model and the potential of probiotic intervention to ameliorate this condition.